2010
DOI: 10.1021/jp911086n
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Dependence of the Kinetic Isotope Effect in the Reaction of Ascorbate with the 2,2,6,6-Tetramethylpiperidine-1-oxyl Radical: Tunnelling in a Small Molecule Reaction

Abstract: The oxidation of ascorbate with the 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) radical in water and water-dioxane mixed solvent has been demonstrated to be a proton-coupled electron transfer (PCET) process, involving hydrogen tunnelling at room temperature. The magnitude of the kinetic isotope effect (KIE) k(H)/k(D) in the reaction increases with decrease of the solvent polarity. The evidence comprise: (a) the spectroscopic and kinetic evidence for the interaction of ascorbate and TEMPO; (b) the observation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 63 publications
2
36
0
Order By: Relevance
“…In par ticular, the KIE value is 10.6-15 for the reaction sty rene peroxy radicals with substituted phenols [33,34], 24 for the reaction of ascorbate with 2,2,6,6 tetrame thylpiperidine 1 oxyl [35], 18 for the vitamin E radi cal with ubiquinol 10 [36], 3-8 for the reaction of ascorbate with the free radical formed from α toco pherol in micellar solutions [37]. Note that the oxida tion of PUFAs is so far the only example in which the KIE value changes nonadditively with the composi tion of the reaction mixture composed of nondeuter ated and deuterated compounds.…”
Section: Oxidation Of a Mixture Of Deuteratedmentioning
confidence: 98%
“…In par ticular, the KIE value is 10.6-15 for the reaction sty rene peroxy radicals with substituted phenols [33,34], 24 for the reaction of ascorbate with 2,2,6,6 tetrame thylpiperidine 1 oxyl [35], 18 for the vitamin E radi cal with ubiquinol 10 [36], 3-8 for the reaction of ascorbate with the free radical formed from α toco pherol in micellar solutions [37]. Note that the oxida tion of PUFAs is so far the only example in which the KIE value changes nonadditively with the composi tion of the reaction mixture composed of nondeuter ated and deuterated compounds.…”
Section: Oxidation Of a Mixture Of Deuteratedmentioning
confidence: 98%
“…The reaction between ascorbate and TEMPO radical was studied experimentally. [50] The mechanism was best explained by proton-coupled electron transfer (PCET) ( Figure 5), where an electron and proton are transferred simultaneously but between different sets of orbitals. This mechanism differs from SPLET, as the electron and proton are transferred in a single elementary step rather than sequentially.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, Nielsen and Ingold found that the β In some types of hydrogen abstraction reactions, the effect of changing the solvent is low. The reaction between ascorbate and 2,2,6,6-tetramethylpiperidine-1-oxyl radical was studied experimentally 49 . The mechanism was best explained by proton-coupled electron transfer (PCET) (Figure 5), where an electron and proton are transferred simultaneously but between different sets of orbitals.…”
Section: Hydrogen Abstractionmentioning
confidence: 99%